Influence of the Parental Family on the Trajectories of Professional Mobility of Postgraduate Students - R. G. Smirnov (Высшее образование в России, 2022)
The article examines the phenomenon of the parental family as a factor influencing the social (professional) mobility of postgraduate students. The influence of the parental family is analyzed in two directions / spheres: 1) the period of study (from the moment of admission to the defense of the dissertation) and 2) the formation of the views and perceptions of postgraduate students about career prospects and opportunities. The empirical base of the study is represented by data from qualitative in-depth interviews with postgraduate students of Moscow universities (N=30). There is proposed differentiation of students in postgraduate school into two groups (“goal-oriented” and “coincidental”), and the following conclusions are drawn: 1) at the initial stage of education, the role and importance of the parental family in the view of postgraduate students is minimal; 2) by the time of completing postgraduate studies, goal-oriented postgraduate students change their minds, recognizing the importance of the family as a supporting factor of social and professional mobility; 3) in contrast to the period of studying in graduate school the parental family becomes a significant factor of mobility in the views and perceptions of postgraduate students about professional prospects and the formation of a career trajectory.